Planar Imaging of Stagnant and Hydrodynamic Fluid using Miniaturized ECT Device - Leow, Pei Ling (International Journal of Integrated Engineering, 2018)
This paper discusses the development of an on chip planar capacitance tomography (ECT) for stagnant and hydrodynamic multiphase fluid monitoring. The 8-electrode planar ECT device is developed based on Lab-on-chip (LOC) or microfluidic device concept. The ECT with LOC application is an improved design to allow ECT to be portable and small scaled measurement. To reconstruct images, ECT measures the permittivity variation within the sensing area. Eight-planar electrodes with dimension of 5.00 mm × 2.08 mm (length × width) are fabricated on printed circuit board (PCB). These electrodes are aligned to circulate 16 mm diameter of sensing area. For stagnant sample, the design of the chamber is simpler from the hydrodynamic flow. The hydrodynamic flow consists with two inlets to allow multiphase flow testing. Fan beam projection technique is utilized with Linear Back Projection (LBP) algorithm to reconstruct images of the substance within the chamber. Time is an important item for hydrodynamic flow compared to stagnant sample to ensure that the data taken is useful to the user. For stagnant experiment, the ECT system able to produce image reconstruction for water – air, oil – water and yeast – glucose samples. For hydrodynamic flow, the test conducted for immiscible water – oil sample, and miscible water – glucose solution is done. The results show the system produce the best result when one liquid is dominating the sensing area.